ANALISIS BIAYA DAN WAKTU PEMBANGUNAN GEDUNG FPEB UPI MENGGUNAKAN SISTEM MODULAR PADA DINDING - Ary Setyawan; Friska Herlina Pakpahan; Setiono Setiono (Matriks Teknik Sipil, 2025)
The conventional development system which is still commonly used in Indonesia is regarded as being ineffective to apply because it is more expensive. In addition to technology advancements, a development method that employs a modular approach is possible to cut down on project expenses and duration. The building process in a modular system result in industrialization, where the construction materials needed are mass-produced. This study compares the time and costs involved in building conventional and modular walls. The costs and times for traditional and modular wall works are being compared in this study using a comparative descriptive methodology. The data was gathered as part of the FPEB Building project at the Indonesian Education University (UPI), and Microsoft Excel will be used to process it. In this study, the usage of lightweight concrete panels as modular wall materials was analyzed for cost and duration effectiveness to establish the percentage of savings. From the data analysis, it was found that the use of lightweight concrete panels walls experienced a cost inefficiency of 6,4%. When viewed from a time perspective, the use of lightweight concrete panels are 45.45% efficient.